(untitled) (Journal of Parents and Teachers, 2013)
The study held by the State Observatory of Scholar Coexistence states that the general situation is acceptable but that there are still situations of break in the cohabitation such as the harassment among equals or “bullying” and the disruption of classes. We need to be proactive and take initiatives to work towards a positive coexistence instead of being reactive. Being proactive means that we need to develop the socio-emotional competences, competences that are necessary to be able to live together positively and also work on the ethical values that make it possible. It is important that parents, teachers and children are involved in every single sector of the educational community. The Coexistence Plan of the school must be a practical and effective instrument for the development of cohabitation.